Evaluation of the program participatory empowerment Gerbangmas-Taskin at Pandak Daun Village, Banjar Regency - Apsari, Lindiya; Soetarto, Endriatmo; Baga, Lukman Muhammad (Jurnal Penyuluhan, 2019)
Gerbangmas-Taskin is a poverty alleviation program in South Kalimantan province with the concept three (human empowerment, economic and the environment). This study aims to analyze the implementationof Gerbangmas-Taskin effectiveness, to evaluate the sustainability of Gerbangmas-Taskinand prioritize participatory empowerment strategy for effectiveness and sustainability of Gerbangmas-Taskin at PandakDaun Village, Banjar Regency. The methods used include descriptive analysis, RAPfish modification (RAPGerbangmas-Taskin) and Analytical Hierarchy Process (AHP). The data consists of primary data obtained from the results of in-depth interview and a questionnaire given to Poor Households (RTM), while the secondary data obtained from the publication of the relevant agencies. The result showed that Gerbangmas-Taskin program did not impact earnings accretion for the beneficiaries of capital. Gerbangmas-Taskin sustainability index is 34.79 % (less sustainability), consist of :Infrastructure by 62.39% (sustainable enough) while economic, social and environmental showed less sustainable, respectively by 36.85%; 30.22% and 27.11%. The main priority in the strategy of the effectiveness and sustainability of Gerbangmas-Taskin program are the coordination and synergy with the section / SKPD (19%) and increasing the capacity of human resources (16%).